Pengaruh Penambahan Ekstrak Herbal Yang Berbeda Pada Pakan Buatan Terhadap Laju Pertumbuhan Dan Kelulushidupan Benih Ikan Nila (Oreochromis niloticus) - Ramlah Rubai; Hasim; Sutianto (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
Nile tilapia (Oreochromis niloticus) is a widely utilized fish species known for its high nutritional value, including protein, fat, vitamins, and minerals. However, feed efficiency remains a significant challenge in Nile tilapia farming. Enhancing feed quality through the addition of herbal extracts, such as turmeric, ginger, and galangal, is a promising solution. This study aimed to evaluate the effects of herbal extract supplementation in feed on the growth in length and weight of Nile tilapia. The research was conducted over 30 days, with measurements of fish length and weight taken every ten days. Four treatments were applied: A (control), B (6 g/kg feed of ginger extract), C (6 g/kg feed of turmeric extract), and D (6 g/kg feed of galangal extract). The results showed that the addition of herbal extracts improved the growth performance of Nile tilapia. Treatment C (turmeric extract) exhibited the highest growth in length (1.01 cm) and the highest absolute weight gain (1.49 g). In conclusion, turmeric extract supplementation demonstrated the most significant impact on enhancing the growth in length and weight of Nile tilapia, making it a viable alternative to improve feed efficiency in aquaculture.